The unconstitutionality plea in Algeria - MAMRI, Nasreddine (Art Law and Accounting Reporter, 2026)
The Algerian constitutional legislator has established a mechanism for the posterior review of the constitutionality of laws under the designation of the "unconstitutionality plea" — a procedure known in French law as the Question Prioritaire de Constitutionnalité (QPC). Article 188 of the 2016 Constitutional Amendment granted, for the first time, the parties to a judicial dispute the right to challenge legislative provisions they claim violate the rights and freedoms guaranteed to them by the Constitution (later re-enacted as Article 195 of the 2020 Constitutional Amendment). The organic law 18-16 subsequently regulated the legislative dimensions of this mechanism by establishing its conditions and modalities of application, followed by Organic Law 22-19 of 25 July 2022, which specifies the notification and referral procedures before the Constitutional Court. To provide a comprehensive examination and critical evaluation of this experience in Algeria, this article is structured around four principal axes. The first examines the unconstitutionality plea in Algeria and situates it within comparative legal frameworks, exploring the extent to which the Algerian legislator has charted a distinct course in regulating this matter. The second axis addresses the conceptual framework of the mechanism, with particular attention to the applicable conditions and standards governing its use. The third axis traces the filtration procedures through which unconstitutionality pleas are screened — first at the level of the lower courts, and then at the level of the Supreme Court or the Council of State. The fourth and final axis offers a critical reading of the decisions issued through this mechanism during both the era of the Constitutional Council and that of the Constitutional Court, presenting a comprehensive inventory of all relevant decisions and comparing the Algerian experience with its French counterpart.
Keywords: Unconstitutionality Plea; Constitutional Review; Constitutional Court; Constitutionality Filtration; QPC; Fundamental Rights and Freedoms; Algeria; France